Book Review: Hannah Frank, Frame by Frame: A Materialist Aesthetics of Animated Cartoons (University of California Press, 2019). Issue 1 (7th June 2021) - Cook, Malcolm
Abstract : Hannah Frank, Frame by Frame : A Materialist Aesthetics of Animated Cartoons (Oakland: University of California Press, 2019), pp. ix–256, ISBN: 9780520303621 (pb), £27.93, DOI: https://doi.org/10.1525/luminos.65 . This book is available as an open source publication at https://luminosoa.org/site/books/m/10.1525/luminos.65/ .